Adverse Childhood Experiences (ACEs) and Gang Involvement Among Juvenile Offenders: Assessing the Mediation Effects of Substance Use and Temperament Deficits. (January 2020) - Wolff, Kevin T.; Baglivio, Michael T.; Klein, Hannah J.; Piquero, Alex R.; DeLisi, Matt; Howell, James C. (Buddy)
A growing body of research has demonstrated the deleterious effects of adverse childhood experiences (ACEs). Less understood is the role of ACEs in gang involvement among juvenile offenders. The current longitudinal study employs a sample of 104, 267 juvenile offenders (mean age of 16, 76% male, 46% Black non-Hispanic, 15.7% Hispanic) to examine the effect of ACE exposure on two different measures of gang involvement by age 18. We use structural equation modeling to test whether higher ACE exposure at Time 1 predicts gang involvement and whether current substance use and/or difficult temperament mediates the ACE-gang involvement relationship. Results indicate ACE exposure at Time 1 predicts gang involvement by age 18, but that much of the effect of ACEs on later gang involvement can be explained by their impact on current substance abuse and difficult temperament. Implications for juvenile justice systems are discussed.